Development of HOTS Oriented Physics Learning Chapter with CBR Approach on Work & Energy Material - Dwi Rika Andriyani; Silvi Yulia Sari; Fanny Rahmatina Rahim; Amali Putra (Department of Physics Universitas Negeri Padang, 2023)
This research focuses on the development of HOTS-oriented physics learning e-book chapters with the CBR approach on effort and energy material for class X SMA which aims to test the validity and practicality of the e-book chapter. By using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation, this form of research is classified as Research and Development (R&D). The e-book chapter validation test process involved 3 UNP Physics lecturers as validators. In the e-book chapter practicality test to teachers, 2 teachers as practitioners from three schools. The practicality test of the e-book chapter to students was carried out on 9 students from one school. From the results of the research data analysis, the conclusions were obtained, first, the HOTS-oriented physics learning e-book chapter with the CBR approach on the material of effort and energy for class X SMA has a validity value of 0.8 with a very valid category. Second, the results of the practicality test of the HOTS-oriented physics learning chapter e-book with the CBR approach on work and energy material for grade X high school have a practicality value of 89.29 with a very practical category. Furthermore, the results of the practicality of the HOTS-oriented physics learning chapter e-book for students with the CBR approach on work & energy material for class X SMA have a practicality value of 87.79 with a very useful category. The practicality and validity results state that the e-book chapter made can be applied to the learning process.